Measuring hope among families impacted by cognitive impairment - Hunsaker, Amanda E. (Dementia (London), 2014)
The current exploratory investigation aims to establish the reliability and validity of a hope measure, the Herth Hope Index (HHI), among families impacted by early cognitive impairment (N=96). Exploratory factor analysis was used to examine the dimensionality of the measure. Bivariate analyses were used to examine construct validity. The sample had moderately high hope scores. A two-factor structure emerged from the factor analysis, explaining 51.44% of the variance. Both factors exhibited strong internal consistency (Cronbach’s alphas ranged from .83 to .86). Satisfaction with social support was positively associated with hope, supporting convergent validity. Neurocognitive status, illness insight and depression were not associated with hope, indicating discriminant validity. Families impacted by cognitive impairment may maintain hope in the face of a potentially progressive illness, regardless of cognitive status. The HHI can be utilized as a reliable and valid measure of hope by practitioners providing support to families impacted by cognitive impairment.